2008
DOI: 10.1101/lm.964708
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids enhance taste aversion memory via actions in the insular cortex and basolateral amygdala

Abstract: It is well established that glucocorticoid hormones strengthen the consolidation of hippocampus-dependent spatial and contextual memory. The present experiments investigated glucocorticoid effects on the long-term formation of conditioned taste aversion (CTA), an associative learning task that does not depend critically on hippocampal function. Corticosterone (1.0 or 3.0 mg/kg) administered subcutaneously to male Sprague-Dawley rats immediately after the pairing of saccharin consumption with the visceral malai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…To determine how HFD exposure during adolescence leads to enhanced consolidation of emotional memories, we investigated the role of glucocorticoids, since previous research has shown that GR activation in the BLA modulates consolidation of emotional memory as well as LTP in lean animals (Roozendaal and McGaugh, 1997;Miranda et al, 2008;Sarabdjitsingh et al, 2012). Moreover, adolescence is a decisive period for maturation of the HPA axis (Spear, 2000;McCormick and Mathews, 2010;Foilb et al, 2011), and previous reports indicate that chronic HFD exposure can alter HPA axis activity (Tannenbaum et al, 1998;Legendre and Harris, 2006;Sharma and Fulton, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To determine how HFD exposure during adolescence leads to enhanced consolidation of emotional memories, we investigated the role of glucocorticoids, since previous research has shown that GR activation in the BLA modulates consolidation of emotional memory as well as LTP in lean animals (Roozendaal and McGaugh, 1997;Miranda et al, 2008;Sarabdjitsingh et al, 2012). Moreover, adolescence is a decisive period for maturation of the HPA axis (Spear, 2000;McCormick and Mathews, 2010;Foilb et al, 2011), and previous reports indicate that chronic HFD exposure can alter HPA axis activity (Tannenbaum et al, 1998;Legendre and Harris, 2006;Sharma and Fulton, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time rapamycin (6 mg/kg, Sigma) or DMSO (0.01%) was administered i.p. We have used a single dose of corticosterone in a range that mimics plasma corticosterone levels induced by stress and facilitates memory formation (Cordero and Sandi 1998;Miranda et al 2008;Atsak et al 2015). Then, the animals were transferred back into their home cage.…”
Section: Fear Conditioningmentioning
confidence: 99%
“…This dose of corticosterone results in an increase in circulating corticosterone levels within the physiological range and enhances memory consolidation (Miranda et al, 2008). The corticosterone and SR141716 mixture was dissolved in 5% polyethylene glycol, 5% tween-80, and 5% ethanol in saline.…”
Section: Drugs and Infusion Proceduresmentioning
confidence: 99%